The Interplay of Humans and Technology in Innovation: How Human Capital, Social Media, and Open Innovation Shape Innovation Performance in the Posthuman Era - Yulianti, Prima; Fahmy, Rahmi; Lukito, Hendra; Games, Donard (Journal of Posthumanism, 2026)
This study explores the role of human capital, social media, and open innovation in shaping innovation performance among Minangkabau culinary entrepreneurs in West Sumatra. Using a qualitative approach through in-depth interviews and field observations across five regions, the study examines how traditional skills and experiential knowledge are transformed through digital technologies. The findings reveal that human capital serves as the primary driver of innovation, while social media mediates open innovation by enabling idea exchange, customer feedback, and network expansion. Human–technology interactions allow entrepreneurs to preserve cultural identity while enhancing market adaptability. This study contributes to the understanding of culturally embedded innovation in the posthuman era.